2020
DOI: 10.1002/ccr3.2636
|View full text |Cite
|
Sign up to set email alerts
|

Serum free light chains and multiple myeloma: Is it time to extend their application?

Abstract: In nonsecretory, oligo‐secretory, and light chain multiple myeloma patients, serial sFLC evaluation could precede biochemical and clinical disease progression, even in extramedullary relapse, thus initiating early treatment with novel anti‐MM agents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…FLC ratio can be normal, especially in pre-myeloma stages with low risk of progression, in younger patients, or in those subjects with concomitant increased of uninvolved light-chain levels [ 45 , 46 , 47 ]; however, this condition is not frequent in active MM, as reported in our case series (only 18% of patients, mostly with concomitant increased of uninvolved FLC), also in accordance with previously published studies [ 47 , 48 ]. Conversely, FCL ratio is abnormal in almost all non-secretory myeloma with a sensitivity close to 100% [ 16 , 17 , 18 , 19 ]. In our case series, we confirmed the high diagnostic potential of sFLC ratio for light-chain MM identification, and we also showed that the standardized values were highly correlated with renal failure, especially in light-chain MM.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…FLC ratio can be normal, especially in pre-myeloma stages with low risk of progression, in younger patients, or in those subjects with concomitant increased of uninvolved light-chain levels [ 45 , 46 , 47 ]; however, this condition is not frequent in active MM, as reported in our case series (only 18% of patients, mostly with concomitant increased of uninvolved FLC), also in accordance with previously published studies [ 47 , 48 ]. Conversely, FCL ratio is abnormal in almost all non-secretory myeloma with a sensitivity close to 100% [ 16 , 17 , 18 , 19 ]. In our case series, we confirmed the high diagnostic potential of sFLC ratio for light-chain MM identification, and we also showed that the standardized values were highly correlated with renal failure, especially in light-chain MM.…”
Section: Discussionmentioning
confidence: 99%
“…Free kappa or lambda chain hyperproduction is an indirect index of clonal plasma cell expansion and proliferation [ 13 ]; therefore, serum FLC ratio is an optimal minimally invasive biomarker of the differential diagnosis of benign and malignant plasma cell disorders [ 14 , 15 ]. Indeed, sFLC is a breakthrough biomarker of MM with a sensitivity close to 100% for non-secretory myeloma, as its FLC ratio is always abnormal, even in the absence of M-protein, thus rendering this marker an optimal tool for monitoring oligo- or non-secretory plasma cell disorders [ 16 , 17 , 18 , 19 ]. Moreover, sFLC is used for screening together with protein electrophoresis, immunofixation, and 24 h urine studies [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…According to IMWG, biochemical relapse should be treated in high-risk patients—i.e., those with aggressive disease at diagnosis or relapse or adverse cytogenetics and short treatment-free interval, or with a suboptimal response—in order to avoid severe symptomatic disease [ 19 , 20 ]. In a previous work, our group has already suggested extending the application of sFLC to first and subsequent relapse, since it had an anticipatory role in clinical relapse, including cases of aggressive non-secretory or oligo-secretory EMD disease [ 21 ]. This suggestion comes from four clinical cases in which sFLC evaluation preceded clinical aggressive relapse.…”
Section: Discussionmentioning
confidence: 99%
“…Shift from negative to positive urine immune-fixation and Bence Jones proteinuria are predictor markers of progression to active MM. 30 , 32 , 33 Dynamic monitoring of sFLC 34 and M component are helpful to identify evolving SMM type, 35 with an emerging prognostic role. 36 Based on the pioneering work of Dr. Dispenzieri and colleagues who evaluated disease progression in 273 SMM patients at Mayo Clinics, an involved/uninvolved FLC ratio of ≥8 is a significant risk factor for progression, 37 and if sFLC ratio rises to ≥ 100, the 2 year risk of progression approaches 80%, thus to be considered a myelomadefining event in the IMWG guidelines.…”
Section: Initial Diagnostic Work-upmentioning
confidence: 99%